The effects of REBT on irrational beliefs, self-determined motivation, and self-efficacy in American Football - Chrysidis, S.; Turner, M. J.; Wood, A. G. (Journal of Sports Sciences, 2020)
It has been suggested in recent research that rational beliefs as conceptualized within rational-emotive behaviour therapy (REBT) can be operationalized as strategic self-talk, but this has yet to be meaningfully investigated. The current study examines the effects of five one-to-one REBT sessions with three amateur American Football athletes to foster rational self-talk. The purpose of the intervention was to reduce the irrational beliefs, but also in line with recent applied REBT research, to increase the self-determined motivation and self-efficacy of the athletes. Using an idiographic single-case, staggered multiple-baseline across participants design, visual analyses revealed meaningful increases in self-determined motivation and self-efficacy, adjunct to decreases in total irrational beliefs across all participants. Social validation data supported these outcomes. These findings add to the growing research indicating that REBT can influence motivational approaches in athletes, such as self-determined motivation and self-efficacy. Results are discussed in relation to processes underlying the mechanisms of change, while also reporting the limitations of the study. The robustness of the research design increases the extent to which target variable changes can be attributed to REBT, but critical reflections are undertaken to assess the veracity of the findings.